Current developments in biotechnology and bioengineering current advances in solid-state fermentation - Pandey, Ashok; Larroche, Christian; Soccol, Carlos Ricardo (Elsevier, 2017)
Current Developments in Biotechnology and Bioengineering: Current Advances in Solid-State Fermentation provides knowledge and information on solid-state fermentation involving the basics of microbiology, biochemistry, molecular biology, genetics and principles of genetic engineering, metabolic engineering and biochemical engineering. This volume of the series is on Solid-State fermentation (SSF), which would cover the basic and applied aspects of SSF processes, including engineering aspects such as design of bioreactors in SSF. The book offers a pool of knowledge on biochemical and microbiological aspects as well as chemical and biological engineering aspects of SSF to provide an integrated knowledge and version to the readers
SECTION A: GENERAL 1. Advances in solid-state fermentation SECTION B: FUNDAMENTAL ASPECTS AND SSF BIOREACTORS 2. Advance in porous characteristics of the solid matrix 3. Microbial physiology in solid state fermentation and aspects of separation of Bioproducts 4. Kinetics and modelling in solid-state fermentation 5. Aspects of design of bioreactors in solid-state fermentation 6. A novel equipment for respirometry applied to solid-state fermentation but also to submerged fermentation 7. Bioreactors for the production of biological control agents produced by solid-state fermentation SECTION C: APPLIED ASPECTS 8. Solid-state fermentation for the production of lipases for environmental and biodiesel applications 9. Solid-state fermentation for the production of cellulases and their applications 10. Solid-state fermentation for the production of proteases and amylases and their applications 11. Solid-state fermentation for laccases production and their applications 12. Agricultural residues as animal feed: protein enrichment and detoxification using solid-state fermentation 13. Advanced solid state fermentation for cost-effective production of fuel ethanol 14. Secondary metabolites production: Physiological advantages in solid-state fermentation 15. Solid-state fermentation for the production of mushrooms 16. Solid-state fermentation for food applications 17. Solid-state fermentation for vermicomposting 18. Solid-state fermentation for the production of organic acids 19. Solid-state fermentation and plant beneficial microorganisms
Keywords: Bioengineering; Biotechnology; Solid-state fermentation